Novel auction-based spectrum sharing scheme with the compensation and motivation mechanism - ZHOU Wei-feng; ZHU Qi (Tongxin xuebao)
A novel spectrum sharing scheme based on the auction theory and the mechanism of compensation and motiva-tion was proposed.Based on the simplified VCG（vickrey-clarke-groves） auction,co-operative competition model was de-veloped which was realized by introducing the cooperative relationship between secondary users and adopting the mecha-nism of monetary compensation and motivation.The novel model shows not only the automatic decision-making character-istics of non-cooperative game model,but also the fairness characteristics of the oligopoly joint model.Theoretical analysis and simulation results evaluate the system performance and verify the correctness and fairness of the proposed scheme.